2018
DOI: 10.1515/roe-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Large Banking Institutions to Systemic Risk: What Do We Know? A Literature Review

Abstract: Against the background of the global financial crisis, we review recent literature on the debate about “too big to fail”. This is (still) one of the key issues in banking literature since it determines the conditions for adequate banking regulation, financial stability and economic welfare. Analyzing 30 papers from 2009 to 2017, our work focusses on the impact of large banks on systemic risk. Large financial institutions can affect systemic risk by either contributing to systemic risk or being extremely expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
0
5
0
1
Order By: Relevance
“…On the other hand, supporters of the concentration-fragility hypothesis argue that the existence of large institutions systematically increases systemic risk (e.g. Moch (2018)). Mishkin (1999) argues that very large banks may be tempted to take on risky investments, as they might be likely to be rescued by the government due to their systemic importance.…”
Section: Related Literaturementioning
confidence: 99%
“…On the other hand, supporters of the concentration-fragility hypothesis argue that the existence of large institutions systematically increases systemic risk (e.g. Moch (2018)). Mishkin (1999) argues that very large banks may be tempted to take on risky investments, as they might be likely to be rescued by the government due to their systemic importance.…”
Section: Related Literaturementioning
confidence: 99%
“…Ini juga membantu dalam menentukan masalah dan celah dalam literatur yang ada dan membantu dalam formulasi hipotesis dan pemahaman tentang area penelitian yang spesifik (Kalkavan 2020). Literature review dapat dilakukan dengan mengakses database publikasi ilmiah, seperti Scopus, Web of Science, dan Google Scholar (Moch 2018). Peneliti juga dapat melakukan pencarian manual melalui jurnal ilmiah dan buku-buku yang terkait.…”
Section: Telaah Literaturunclassified
“…The classification of SIBs and shocks coming from SIBs have been at the helm in designing and implementing macroprudential policies (such as the systemic risk buffer) since the Global Financial Crisis (GFC) of 2007-2008. Since the financial meltdown of the GFC (Silva et al, 2017), financial institutions' insolvencies, and lowering the availability of credit in the global economies, several theoretical studies have found a link between systemically important banks and their contribution to systemic risk (e.g., Zhou, 2009;Caccioli et al, 2012;Elliott et al, 2014). Evidence shows that SIBs, regarded as too big to fail, inflict a negative externality on the system and endanger financial stability (Moch, 2018). In a highly interconnected banking system, the failure of a large bank could lead to systemic failure exposing the dependencies: the proportion of losses in a failed bank's portfolio will be transferred to other banks through the interbank market, the payment system, or through asset prices.…”
Section: Introductionmentioning
confidence: 99%
“…define systemic risk as a state of simultaneous distress of the financial system, resulting in liquidity and credit dry ups, not only for the financial sector but also for the real economy. In addition to this,Adrian and Brunnermeier (2016),Richardson (2009), andHansen (2013) entail that the failure of one bank can lead to the malfunction of the capital market, the disorganisation and inefficient allocation of capital and credit supply to the real economy.2 Benoit et al, (2017) andMoch (2018) provide a more detailed survey of the theoretical literature on the sources of systemic risk.…”
mentioning
confidence: 99%